2018
DOI: 10.5194/bg-15-5733-2018
|View full text |Cite
|
Sign up to set email alerts
|

Potential for phenol biodegradation in cloud waters

Abstract: Abstract. Phenol is toxic and can be found in many environments, in particular in the atmosphere due to its high volatility. It can be emitted directly from manufacturing processes or natural sources, and it can also result from benzene oxidation. Although phenol biodegradation by microorganisms has been studied in many environments, the cloud medium has not been investigated yet as the discovery of active microorganisms in cloud is rather recent. The main objective of this work was to evaluate the potential d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 65 publications
3
22
0
Order By: Relevance
“…Comparison of previous global estimates of cloud coverage of 60 % (Pruppacher and Jaenicke, 1995) and the volume fraction of liquid clouds within the atmosphere of 15 % (Lelieveld and Crutzen, 1990) generally supports this relationship. The resulting F cloud values are summarized in Table 2 together with the cloud coverage data (F clc ) and the percentage area fraction of each ecosystem of the Earth's surface, taken from Burrows et al (2009b) and originally obtained from Olson (1992).…”
Section: Time Fractions Of Microbial Processes In Clouds (F Cloud )supporting
confidence: 62%
See 1 more Smart Citation
“…Comparison of previous global estimates of cloud coverage of 60 % (Pruppacher and Jaenicke, 1995) and the volume fraction of liquid clouds within the atmosphere of 15 % (Lelieveld and Crutzen, 1990) generally supports this relationship. The resulting F cloud values are summarized in Table 2 together with the cloud coverage data (F clc ) and the percentage area fraction of each ecosystem of the Earth's surface, taken from Burrows et al (2009b) and originally obtained from Olson (1992).…”
Section: Time Fractions Of Microbial Processes In Clouds (F Cloud )supporting
confidence: 62%
“…These substrates include organics (e.g., carboxylic acids, sugars); other elements (e.g., nitrogen, phosphorous, potassium, metals) are also needed and exist in bioavailable forms in cloud water. The biotransformation of formate, acetate, succinate, lactate, oxalate, formaldehyde (Ariya et al, 2002;Vaïtilingom et al, 2010), phenol (Lallement et al, 2018), and methane (Šantl-Temkiv et al, 2013) by bacteria and fungi was studied in aqueous solutions mimicking the typical chemical composition of cloud water, and it was suggested that under specific conditions microbial processes might be competitive to chemical radical processes as sinks for these compounds (Delort et al, 2010;Vaïtilingom et al, 2011Vaïtilingom et al, , 2013. The efficiency of such metabolic processes strongly depends on the bacteria types, substrates, and their availability within the cloud droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Clouds likely offer a more hospitable environment due to water availability and nutrients (Delort et al 2017;Deguillaume et al 2008;Bianco et al 2016). Bacteria might be able to multiply (Sattler et al 2001) and degrade substances (Lallement et al 2018) in cloud doplets.…”
Section: Introductionmentioning
confidence: 99%
“…(Bianco et al, 2019b;Vaïtilingom et al, 2011Vaïtilingom et al, , 2013. They are also able to degrade pollutants such as phenols (Lallement et al, 2018b). Moreover, they interact with reactive oxygen species, thus playing another role in cloud chemistry: they destroy oxidants that can potentially damage cells, reducing the concentration of precursors (H 2 O 2 in particular) of reactive oxygen species (Vaïtilingom et al, 2013;Wirgot et al, 2017).…”
Section: Cloudmentioning
confidence: 99%